Accelerated decline in motor suppression in patients with cerebrovascular disorders: A kinetic analysis using the square-tracing task. - Kimoto, Shoko; Naito, Yasuo; Nishikawa, Takashi (NeuroRehabilitation, 2024)
BACKGROUND: Patients with cerebrovascular disorders (CVDs) tend to exhibit impulsive behaviour without controlling their movements, leading to difficulty in performing activities of daily living and an increased risk of accidents. This hastiness, termed 'pacing impairment', has been studied but is not fully understood. OBJECTIVE: To experimentally examine the kinetic features of pacing impairment by focusing on changes in speed and investigating neuropsychological substrates. METHODS: We instructed 53 inpatients with CVDs, 20 orthopaedic inpatients, and 20 healthy participants to trace a 200 mm-sided square as slowly as possible for 120 seconds. We measured the tracing length and mean acceleration and examined the relationship between these measurements, neuropsychological symptoms, and lesion sites. RESULTS: Gradual acceleration in drawing, i.e., decline in motor suppression, was observed more frequently in the CVD group than in the control groups. Excessive acceleration was associated with unilateral spatial neglect, frontal lobe signs, and attention disorders but not with motor impersistence. Additionally, the incidence of excessive acceleration did not differ between left and right hemisphere lesion subgroups and was not associated with any specific lesion site. CONCLUSION: Pacing impairment can manifest as general or holistic deficits in attentional function widely distributed throughout the cerebral hemispheres.